Accuracy of pre- and postnatal assessment of gestational age. Issue 11 (November 1979) - Mitchell, D
Abstract : The gestational age at delivery in a group of 20 neonates was estimated prenatally from measurements of the biparietal diameter made by ultrasound during pregnancy, and postnatally from the newborn infant's neurological and external physical criteria or maturity using the method of Dubowitz et al. (1970). These two assessments were compared with the gestational age at delivery calculated from the date of the last menstrual period (LMP) in mothers certain of their dates. Gestational age derived from the ultrasound data correlated well with that derived from the mother's LMP, and much better than did gestational age derived from the postnatal scoring system.